Moisture absorption and mechanical degradation of hybrid Pennisetum purpureum/glass–epoxy composites. (1st May 2016) - Ridzuan, M.J.M.; Abdul Majid, M.S.; Afendi, M.; Azduwin, K.; Amin, N.A.M.; Zahri, J.M.; Gibson, A.G.
Abstract: The effect of moisture absorption on the mechanical degradation of hybrid Pennisetum purpureum /glass–epoxy composites was investigated. The hybrid P. purpureum /glass–epoxy composites plates were manufactured by the vacuum infusion method using epoxy resin as a matrix. Following 50 h of water immersion, the hybrid composite specimens were tested. The moisture content reduced as the glass fibre content increased. The wet and dry hybrid composite specimens were subjected to tensile and flexural tests. The incorporation of the glass fibre into the P. purpureum –epoxy composites enhanced their tensile and flexural strength, as well as their modulus. The tensile and flexural strengths of the hybrid P. purpureum /glass–epoxy composites (24/6–70 vol%) were 43 and 60 MPa, respectively. However, the tensile and flexural properties significantly degraded under wet conditions. Using field emission scanning electron microscopy (FESEM), morphological analysis was performed to observe the fracture behaviour of the specimens and the effect of water molecules.